2010
DOI: 10.1016/j.brainres.2010.03.114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of central projections from amylin-activated neurons to the lateral hypothalamus

Abstract: The ability of the pancreatic hormone amylin to inhibit food intake relies on a direct activation of the area postrema (AP). This activation is synaptically transmitted to the nucleus of the solitary tract (NTS), the lateral parabrachial nucleus (LPB), the central amygdaloid nucleus (Ce) and the lateral bed nucleus of stria terminalis (BSTL). Interestingly, neurons of the rostro-dorsal lateral hypothalamic area (dLHA), which are activated during fasting, are inhibited by peripheral amylin, although they lack a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 67 publications
0
49
0
Order By: Relevance
“…Lesions of the respective brain areas (AP, NTS, and LPB) abolished amylin's effect, and activation (as indicated by c-Fos) was absent in brain areas rostral to the lesion (e.g., in the NTS, LPB, and CeA in AP lesioned rats, or in the CeA in LPB lesioned rats). The direct link between the respective brain areas was confirmed by the use of anterograde and retrograde neuronal tracers; these studies also identified the LPB as the primary relay between the hindbrain and the hypothalamus, including the lateral hypothalamic area, where amylin reduces fasting-induced c-Fos expression Potes et al, 2010a) and the VMH (Mollet et al, 2003b;Roth et al, 2008a;Turek et al, 2010). The latter area received more attention in recent years due to the possible role of the VMH in mediating the interaction between amylin and leptin (see section IX.A).…”
Section: Neuroaxis Activation By Amylinmentioning
confidence: 80%
See 2 more Smart Citations
“…Lesions of the respective brain areas (AP, NTS, and LPB) abolished amylin's effect, and activation (as indicated by c-Fos) was absent in brain areas rostral to the lesion (e.g., in the NTS, LPB, and CeA in AP lesioned rats, or in the CeA in LPB lesioned rats). The direct link between the respective brain areas was confirmed by the use of anterograde and retrograde neuronal tracers; these studies also identified the LPB as the primary relay between the hindbrain and the hypothalamus, including the lateral hypothalamic area, where amylin reduces fasting-induced c-Fos expression Potes et al, 2010a) and the VMH (Mollet et al, 2003b;Roth et al, 2008a;Turek et al, 2010). The latter area received more attention in recent years due to the possible role of the VMH in mediating the interaction between amylin and leptin (see section IX.A).…”
Section: Neuroaxis Activation By Amylinmentioning
confidence: 80%
“…A frequent marker to define stimulus-activated brain areas is based on the expression of the immediate early gene product c-Fos (Rowland et al, 1997;Becskei et al, 2004;Riediger et al, 2004;Mack et al, 2010;Potes et al, 2010a). It is important to note that c-Fos expression does not necessarily have a functional correlate for a behavioral effect of the same stimulus (e.g., see Züger et al, 2013).…”
Section: B Brainstem Mechanisms Mediating Amylin Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, brain structures shown to be synaptically activated by amylin (45,50), namely the NTS, LPB, Ce, and BSTL, also showed increased ERK1/2 phosphorylation after amylin treatment. Fifth, a blockade of the ERK cascade in the AP by injection of the MEK1/2 inhibitor U0126 into the 4V reduced the number of neurons displaying amylin-induced pERK in the AP by about 30%.…”
Section: Discussionmentioning
confidence: 92%
“…It is, however, important to note that the pERK signal in the LPB appeared to follow similar time lines as in the AP, i.e., there was a higher degree of stimulation at the 15-min time point. Our recent tracing studies showed that there is a prominent projection from the AP to the LPB (45). These studies had suggested that the amylin signal may at least in part be transmitted directly from the AP to the LPB, and that the indirect transmission via the NTS may be less important.…”
Section: Discussionmentioning
confidence: 98%